Pengaruh Pendekatan Realistic Mathematics Education terhadap Hasil Belajar Siswa Kelas IV SDN 11 Pontianak Kota - Amaliawan, Nur; Kartono, Kartono; Ghasya, Dyoty Auliya Vilda (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
The Realistic Mathematics Education (RME) approach is an approach developed by the Freudenthal Institute, Utrecht University in the Netherlands. This research focuses on the learning outcomes of fourth grade students of SDN 11 Pontianak Kota which aims to answer three questions: (1) Student learning outcomes using the RME approach, (2) Student learning outcomes without using the RME approach, and (3) The average difference in student learning outcomes. The research method used quantitative research of quasi-experimental type with Nonequivalent control group design and data collection techniques through measurement techniques with instruments in the form of essay questions. The results of the research findings (1) Student learning outcomes using the RME approach were obtained at the pre-test value with an average of 11.76 and at the post-test value with an average of 73.80, (2) Student learning outcomes without using the RME approach were obtained at the pre-test value with an average of 14.12 and at the post-test value with an average of 50.40, and (3) Based on calculations using the N-Gain formula, the average learning outcomes were 70.87 and 42.39. So it is concluded that the class using the Realistic Mathematics Eduation (RME) approach is better than the class without the Realistic Mathematics Eduation (RME) approach.